Penanaman Bibit Pohon Mangrove Didesa Regemuk Kecamatan Pantai Labu Kabupaten Deli Serdang - Siswa Panjang Hernos; Gustami Harahap; Darianto (Amaliah: Jurnal Pengabdian Kepada Masyarakat, 2025)
This community service activity aims to address ecosystem damage, coastal erosion, climate change, reduced fish catch, declining water quality, loss of biodiversity, and environmental pollution, as well as support coastal community welfare. able to provide a positive stimulus to the community about the importance of mangrove forests in coastal areas, which impacts the socio-economic conditions of the Regemuk village community. The activity was carried out by applying science and technology directly to strengthen mangrove plants. The results obtained from the activity are that this community service can provide a positive stimulus to the community about the importance of mangrove forests in coastal areas, which impacts the socio-economic conditions of the Regemuk village community, and the planting of mangroves in coastal areas will maintain ecological functions such as providing habitat for marine animals to shelter, food chains, and breeding, as well as protecting Pantai Labu from sea water abrasion.